Hollow aramid aerogel fiber and preparation method thereof
By combining wet spinning and chemical foaming methods, the structure of hollow aramid aerogel fiber is regulated, and the problem of low porosity in the prior art is solved, fiber preparation with high porosity and adjustable pores is achieved, and its application in multiple fields is expanded.
Patent Information
- Application Number
- CN202510185028.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-19
AI Technical Summary
The prior art is difficult to prepare hollow aramid aerogel fibers with adjustable hollow pores with high porosity, which limits its application in the fields of adsorption, separation, filtration and thermal management.
By combining wet spinning and chemical foaming methods, the inner diameter, outer diameter and wall thickness of the fibers and the pore size on the fiber wall are adjusted to form hollow structural fibers with high porosity. The specific steps include placing the aramid fibers in a alkali-containing solution, stirring, adding a foaming agent to form a spinning liquid, extruding to a solidification bath to solidify, and then undergoing solvent replacement and drying.
It has achieved high porosity and adjustable hollow pores, and has flame retardant and heat insulation, high mechanical strength and other properties, which has expanded its application range and performance in many fields.
Smart Images

Figure CN119877138A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hollow gel fibers, and in particular to a hollow aramid aerogel fiber and a preparation method thereof. Background Art
[0002] Hollow fiber porous fiber is a kind of nanofiber material with a three-dimensional network structure of tubular cavities in the fiber axis. It has ultra-high porosity, large specific surface area, ultra-low density, excellent mechanical properties and wearability. It has important application value in many fields such as textile, environment, energy conversion and storage, thermal protection, infrared stealth, electromagnetic shielding, etc.
[0003] At present, the preparation technologies of hollow porous fibers mainly include shaped spinneret melt spinning and wet coaxial solution spinning. Both shaped spinneret and coaxial spinning require complex design of equipment components, which are limited by the structure of spinneret / spinning head, so it is difficult to efficiently prepare fibers with complex porous structures. CN202410298279.X discloses a hollow aerogel fiber and a preparation method thereof at room temperature and pressure. The patent provides a preparation method for the hollow aerogel fiber, including preparing a hollow fiber with a porous aerogel structure by synchronously causing non-solvent phase separation inside and outside the fiber at room temperature and pressure, using a coaxial extrusion device, using a non-solvent core liquid for the inner core, and a polymer / solvent solution for the outer layer, which are then injected into a coagulation bath for coagulation and forming, and then dried to obtain the hollow aerogel fiber. However, the material prepared by this method has mostly closed pores, and it can be seen from its coagulation principle and morphology photos that the porosity of the material is relatively low, which is not conducive to the performance of the hollow fiber; Chinese invention patent CN201910933044.2 discloses a graphene aerogel hollow fiber, its preparation method and application, but the graphene aerogel material is usually brittle, and the pore structure, morphology and distribution cannot be controlled, it is difficult to solve the problems of high selectivity and high flux at the same time, and the scope of application is narrow.
[0004] Therefore, how to prepare hollow aramid aerogel fibers with high porosity and adjustable hollow channels to meet application requirements in adsorption, separation, filtration and thermal management is an urgent problem to be solved. Summary of the invention
[0005] To solve the above problems, the present invention provides a hollow aramid aerogel fiber and a preparation method thereof. By combining wet spinning with a chemical foaming method, the inner diameter, outer diameter and wall thickness of the fiber and the pore size on the fiber wall are regulated to form a hollow structural fiber with a high porosity, thereby improving and expanding the performance and application range of the aerogel fiber in the prior art.
[0006] In order to achieve the above-mentioned invention object, the present invention provides the following technical solutions:
[0007] In one aspect, the present invention provides a method for preparing a hollow aramid aerogel fiber, comprising the following steps:
[0008] S1. The aramid fiber is placed in an alkali solution and stirred to obtain an aramid nanofiber dispersion;
[0009] S2. adding a foaming agent to the aramid nanofiber dispersion to obtain a spinning solution;
[0010] S3. Extruding the spinning solution into a mixed coagulation bath to obtain a hollow aramid wet gel fiber;
[0011] S4. The aramid wet gel fiber is subjected to solvent replacement and dried to obtain a hollow aramid aerogel fiber.
[0012] In some specific embodiments, the aramid fiber may be waste aramid fiber.
[0013] In some specific embodiments, wet spinning is combined with a chemical foaming method, and a chemical foaming agent that reacts quickly to generate carbon dioxide is selected and mixed with an aramid nanofiber dispersion to prepare a spinning solution, which is then extruded into an acidic aqueous solution by wet spinning to generate carbon dioxide gas, which squeezes the internal solution, thereby forming a hollow structural fiber with a high porosity.
[0014] Further, in S1, the length of the aramid fiber is 1-20 mm, for example, 1-15 mm, or 1-12 mm, or 1-10 mm, or 3-10 mm, or 3-8 mm, or 4-7 mm, such as 5 mm.
[0015] Furthermore, in S1, the alkali-containing solution is a polar organic solution containing an alkaline substance; and the mass volume ratio of the aramid fiber, the alkaline substance and the polar solvent is (1-10) g: (10-20) g: (300-500) mL.
[0016] Further, in S1, the aramid fiber is selected from one or more of para-aramid fiber, heterocyclic aramid fiber, and meta-aramid fiber; aramid nanofiber is selected as the polymer material, which has excellent high strength and high modulus mechanical properties, excellent thermal stability and flame retardant properties, high chemical stability and corrosion resistance, so that the prepared high-porosity porous fiber has flame retardant, heat insulation, high mechanical strength and other properties;
[0017] Further, the alkaline substance is selected from one or more of potassium hydroxide, sodium hydroxide, sodium ethoxide, potassium ethoxide, potassium tert-butoxide or lithium chloride;
[0018] Furthermore, the polar solvent is selected from one or more of DMSO, DMF, NMP or DMAc.
[0019] Further, in S2, the foaming agent is an alkaline foaming agent;
[0020] In some specific embodiments, the foaming agent is selected from one or more of carbonates and bicarbonates; in a preferred embodiment, the foaming agent is selected from one or more of sodium carbonate, sodium bicarbonate, potassium bicarbonate, and ammonium bicarbonate; in a more preferred embodiment, the foaming agent is sodium carbonate.
[0021] Further, in S2, the amount of the foaming agent added is 0.25-15wt% of the total mass;
[0022] In some specific embodiments, the foaming agent is added in an amount of 0.5-12 wt% of the total mass;
[0023] In some preferred embodiments, the amount of the foaming agent added is 1-10 wt % of the total mass; in a more preferred embodiment, the amount of the foaming agent added is 1-8 wt % of the total mass.
[0024] Furthermore, in S3, the coagulation bath is selected from any one or more of sulfuric acid, hydrochloric acid, formic acid, acetic acid, oxalic acid, citric acid, phosphoric acid, and tartaric acid; in some preferred embodiments, the coagulation bath is selected from any one or more of sulfuric acid, hydrochloric acid, acetic acid, and phosphoric acid.
[0025] Furthermore, in S4, the drying method is selected from supercritical CO 2 A combination of drying, freeze drying, vacuum drying or the like;
[0026] In some preferred embodiments, the drying method is selected from supercritical CO 2 One of drying and freeze drying.
[0027] In a second aspect, the present invention provides a hollow aramid aerogel fiber, which is prepared by the above method, wherein the middle part of the hollow aramid aerogel fiber is a hollow structure, and the fiber wall is a nanoporous structure.
[0028] Furthermore, the outer diameter of the fiber is 370 μm-430 μm, the inner diameter is 20 μm-300 μm, and the nanopore diameter is less than 200 nm.
[0029] The hollow aramid aerogel fiber provided by the present invention can be modified by filling with functional materials, heat-treated and hydrophobized according to the environment, and can be used in the fields of phase change material adsorption, water-oil separation, filtration, seawater desalination, water treatment, high thermal insulation, energy storage, etc., which greatly expands and improves the application range and performance of aerogels and hollow fiber membranes.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The present invention combines a wet spinning method with a chemical foaming method, and by adjusting the raw materials and process parameters, a hollow aramid aerogel fiber with high porosity and adjustable hollow channels can be obtained, which has high selectivity and high flux, as well as flame retardancy, heat insulation, high mechanical strength and other properties;
[0032] (2) The method for preparing hollow aramid aerogel fibers with high porosity provided by the present invention does not require complicated synthesis technology, has a simple process, low energy consumption, low production cost, and is suitable for large-scale production and application;
[0033] (3) The hollow aramid aerogel fiber provided by the present invention has a hollow structure in the middle and a nanoporous structure in the fiber wall. The fiber wall has a large specific surface area and a high porosity, and the hollow tube diameter can be adjusted as needed, which has extremely strong designability.
[0034] Instruction Manual
[0035] Figure 1 is an optical photograph of the hollow aramid aerogel fiber of the present invention;
[0036] Figure 2 is a scanning electron microscope image of a hollow aramid aerogel fiber according to an embodiment of the present invention;
[0037] Figure 3 It is a comparative diagram of the morphological characterization of the hollow aramid aerogel fiber of the present invention. DETAILED DESCRIPTION
[0038] In order to make those skilled in the art better understand the technical scheme of the present invention, the present invention is described in detail below in conjunction with specific embodiments. The experimental methods for which specific conditions are not indicated in the following examples are usually carried out under normal conditions or according to the conditions recommended by the manufacturer. The test materials used in the following examples, unless otherwise specified, are purchased from conventional biochemical reagent stores. Unless otherwise specified, percentages and parts are calculated by weight. Unless otherwise defined, all professional and scientific terms used in the text have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar to or equal to the recorded content can all be applied to the present invention. The preferred implementation methods and materials described in the text are only for demonstration purposes.
[0039] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0040] Based on the present invention, the hollow aramid aerogel fiber uses aramid nanofibers and a chemical foaming agent that generates carbon dioxide faster as raw materials, combines wet spinning with chemical foaming methods, dissolves the foaming agent in the spinning solution, and extrudes it into an acidic aqueous solution through wet spinning to generate carbon dioxide gas to squeeze the internal solution, thereby forming a hollow structural fiber with high porosity.
[0041] See also Figure 1 , which is a real photo of the hollow aramid aerogel fiber prepared in the present invention.
[0042] See also Figure 2 , which is a scanning electron microscope image of the hollow aramid aerogel fiber prepared by the present invention, it can be seen that the outer diameter of the hollow aramid aerogel fiber prepared by the present invention is 370μm-430μm, the inner diameter is 20μm-300μm, and the nanopore diameter is less than 200nm.
[0043] Based on the present invention, the hollow aramid aerogel fiber is prepared by the following steps: placing the aramid fiber in an alkali-containing solution and stirring it to obtain an aramid nanofiber dispersion; adding a foaming agent to the aramid nanofiber dispersion to obtain a spinning solution; extruding and spinning the spinning solution into a mixed coagulation bath, wherein the foaming agent generates carbon dioxide gas in the acidic coagulation solution and squeezes the internal solution to form a hollow structure aramid wet gel fiber with high porosity; and replacing the aramid wet gel fiber with a solvent and drying it to obtain the hollow aramid aerogel fiber.
[0044] Based on the present invention, the length of the aramid fiber is 1-20 mm; in some preferred embodiments, the length of the aramid fiber is 1-15 mm; or 1-12 mm; or 1-10 mm; or 3-10 mm; or 3-8 mm; or 4-7 mm; in some more preferred embodiments, the length of the aramid fiber is 5 mm.
[0045] Based on the present invention, the alkali-containing solution is a polar solution containing an alkaline substance; the mass volume ratio of the aramid fiber, the alkaline substance and the polar solvent is (1-10) g: (10-20) g: (300-500) mL.
[0046] Based on the present invention, the aramid fiber is selected from one or more of para-aramid fiber, heterocyclic aramid fiber, and meta-aramid fiber; in some preferred embodiments, the aramid fiber is selected from para-aramid fiber or heterocyclic aramid fiber; aramid nanofiber is selected as the polymer material, which has excellent high-strength and high-modulus mechanical properties, excellent thermal stability and flame retardant properties, high chemical stability and corrosion resistance, so that the prepared high-porosity porous fiber has flame retardant, heat insulation, high mechanical strength and other properties.
[0047] Based on the present invention, the alkaline substance is selected from one or more of potassium hydroxide, sodium hydroxide, sodium ethoxide, potassium ethoxide, sodium tert-butoxide or potassium tert-butoxide; in specific experiments, a reasonable selection can be made according to the situation, and will not be repeated here one by one.
[0048] Based on the present invention, the polar solvent is selected from one or more of DMSO, DMF, NMP or DMAc. In specific experiments, a reasonable selection can be made according to the situation, and will not be described one by one here.
[0049] Based on the present invention, in S2, the foaming agent is an alkaline foaming agent;
[0050] Based on the present invention, the foaming agent is selected from one or more of carbonates and bicarbonates; in some preferred embodiments, the foaming agent is selected from one or more of sodium carbonate, sodium bicarbonate, potassium bicarbonate, and ammonium bicarbonate; in some more preferred embodiments, the foaming agent is sodium carbonate.
[0051] Based on the present invention, the amount of the foaming agent added is 0.25-15wt% of the total mass; in some specific embodiments, the amount of the foaming agent added is 0.5-12wt% of the total mass; in some preferred embodiments, the amount of the foaming agent added is 1-10wt% of the total mass; in a more preferred embodiment, the amount of the foaming agent added is 1-8wt% of the total mass.
[0052] Based on the present invention, the coagulation bath is selected from any one or more of sulfuric acid, hydrochloric acid, formic acid, acetic acid, oxalic acid, citric acid, phosphoric acid, and tartaric acid; in some preferred embodiments, the coagulation bath is selected from any one or more of sulfuric acid, hydrochloric acid, acetic acid, and phosphoric acid.
[0053] Based on the present invention, the drying method is selected from supercritical CO 2 A combination of one or more of drying, freeze drying or atmospheric pressure drying;
[0054] In some preferred embodiments, the drying method is selected from supercritical CO 2 One of drying and freeze drying.
[0055] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0056] Example 1
[0057] After KOH was dissolved in water, DMSO was added, and after ultrasonic dispersion, heterocyclic aramid staple fibers with a length of 4-7 mm were added and stirred evenly. After standing for 24 hours, the mixture was stirred evenly for 24 hours to prepare a dark brown-red aramid nanofiber dispersion (ANF), wherein the ratio of aramid staple fibers: KOH: DMSO was 8 g: 16 g: 400 mL; sodium carbonate was then added to the ANF and stirred for 2 hours to prepare a spinning solution with a sodium carbonate concentration of 1 wt%; the spinning solution was transferred to a wet spinning device, the extrusion speed was set to 600 r / min, the negative draft winding rate was set to 500 r / min, and the spinning solution was extruded into a coagulation bath containing 10 wt% acetic acid, the spinning solution underwent an in-situ dynamic sol-gel transition in the coagulation bath, and the sodium carbonate reacted with the acid to foam to obtain a hollow aramid gel fiber; water was used as a displacement solvent, the aramid gel fiber was immersed in an ethanol displacement solvent for solvent displacement, and then supercritical CO 2 Drying, supercritical temperature and pressure are 35°C and 9.5MPa respectively, and hollow aramid aerogel fiber is obtained after reducing pressure and temperature. The obtained hollow aramid aerogel fiber is subjected to mechanical property testing, and the tensile strength of the hollow aramid aerogel fiber is measured to be 4.6MPa.
[0058] Example 2
[0059] After KOH was dissolved in water, DMSO was added, and after ultrasonic dispersion, Kevlar aramid staple fibers with a length of 4-7 cm were added and stirred evenly. After standing for 24 hours and mechanically stirred for 3 days, a dark brown-red aramid nanofiber dispersion (ANF) was prepared, wherein the ratio of aramid staple fibers: KOH: DMSO was 16 g: 16 g: 400 mL; sodium carbonate was then added to the ANF and stirred for 4 hours to prepare a spinning solution with a sodium bicarbonate concentration of 2 wt%; the spinning solution was transferred to a wet spinning device, the extrusion speed was set to 600 r / min, the negative draft winding rate was set to 500 r / min, and the spinning solution was extruded into a coagulation bath containing 10 wt% acetic acid, the spinning solution underwent an in-situ dynamic sol-gel transition in the coagulation bath, and sodium bicarbonate reacted with the acid to foam to obtain a hollow aramid gel fiber; water was used as a displacement solvent, the aramid gel fiber was immersed in the displacement solvent for solvent displacement, and then supercritical CO 2 Drying, supercritical temperature and pressure are 35°C and 9.5MPa respectively, and hollow aramid aerogel fiber is obtained after reducing pressure and temperature. The obtained hollow aramid aerogel fiber is subjected to mechanical property testing, and the tensile strength of the hollow aramid aerogel fiber is measured to be 3.4MPa.
[0060] Example 3
[0061] After KOH was dissolved in water, DMSO was added. After ultrasonic dispersion, Kevlar aramid staple fibers with a length of 4-7 mm were added and stirred evenly. After standing for 24 hours, mechanical stirring was performed for 3 days to prepare a clear yellow aramid nanofiber dispersion (ANF), in which the ratio of aramid staple fibers: KOH: DMSO was 8g: 16g: 400mL. Sodium carbonate was then added to the ANF and stirred for 6 hours to prepare a spinning solution with a sodium carbonate concentration of 4wt%. The spinning solution was transferred to a wet spinning device and an extruder was set. The spinning speed is controlled at 600r / min, the negative draft winding rate is 500r / min, the spinning solution is extruded into a coagulation bath containing 10wt% acetic acid, and the spinning solution undergoes an in-situ dynamic sol-gel transformation in the coagulation bath to obtain a hollow aramid gel fiber; water is used as a displacement solvent, and the aramid gel fiber is immersed in the displacement solvent for solvent displacement, followed by supercritical drying, the supercritical temperature and pressure are 35°C and 9.5MPa, respectively, and the hollow aramid aerogel fiber is obtained after the pressure and temperature are reduced. The obtained hollow aramid aerogel fiber is tested for performance, and the tensile strength of the hollow aramid aerogel fiber is measured to be 3.2MPa, the porosity is 95%, and the specific surface area is 208.2035m2 / g.
[0062] Example 4
[0063] After KOH was dissolved in water, DMSO was added, and after ultrasonic dispersion, 4-7mm meta-aramid staple fibers were added and stirred evenly. After standing for 24 hours, mechanical stirring was performed for 24 hours to prepare a clear yellow aramid nanofiber dispersion (ANF), wherein the ratio of aramid staple fibers: KOH: DMSO was 32g: 16g: 400mL; sodium carbonate was then added to the ANF and stirred for 2 hours to prepare a spinning solution with a sodium carbonate concentration of 6wt%; the spinning solution was transferred to a wet spinning device, the extrusion speed was set to 600r / min, the negative draft winding rate was set to 500r / min, and the spinning solution was extruded into a coagulation bath containing 20wt% acetic acid, and the spinning solution underwent an in-situ dynamic sol-gel transition in the coagulation bath to obtain a hollow aramid gel fiber. A 25wt% tert-butyl alcohol aqueous solution was used as a displacement solvent, and the aramid gel fiber was immersed in the displacement solvent for solvent displacement. Freeze drying was used to freeze the hydrogel fiber into a solid state at a low temperature of -20°C, and then the hollow aramid aerogel fiber was obtained after drying in a low temperature vacuum environment for 24 hours. The obtained hollow aramid aerogel fiber was tested for its performance, and the tensile strength of the hollow aramid aerogel fiber was measured to be 3.2MPa and the porosity was 96%.
[0064] Example 5
[0065] After KOH was dissolved in water, DMSO was added. After ultrasonic dispersion, Kevlar aramid staple fibers with a length of 4-7 mm were added and stirred evenly. Mechanical stirring was performed for 3 days to prepare a dark brown-red aramid nanofiber dispersion (ANF), in which the ratio of aramid staple fibers: KOH: DMSO was 8 g: 16 g: 400 mL. Sodium carbonate was then added to the ANF and stirred for 6 h to prepare a spinning solution with a sodium carbonate concentration of 8 wt%. The spinning solution was transferred to a wet spinning device and the extrusion speed was set. The spinning solution was controlled to be 600r / min, the negative draft winding rate was 500r / min, and the spinning solution was extruded into a coagulation bath containing 5wt% hydrochloric acid. The spinning solution underwent an in-situ dynamic sol-gel transformation in the coagulation bath to obtain a hollow aramid gel fiber; water was used as a displacement solvent, and the aramid gel fiber was immersed in the displacement solvent for solvent displacement, followed by supercritical drying. The supercritical temperature and pressure were 35°C and 9.5MPa, respectively. After reducing the pressure and temperature, the hollow aramid aerogel fiber was obtained. The mechanical properties of the obtained hollow aramid aerogel fiber were tested, and the tensile strength of the hollow aramid aerogel fiber was measured to be 2.6MPa.
[0066] Example 6
[0067] Potassium tert-butoxide is added to DMAc, and after ultrasonic dispersion, Kevlar aramid staple fibers with a length of 1-3 mm are added and stirred evenly, and mechanical stirring is performed for 3 days to prepare a dark brown-red aramid nanofiber dispersion (ANF), wherein the ratio of aramid staple fibers: potassium tert-butoxide: DMAc is 5g:12g:300mL; sodium carbonate is then added to the ANF and stirred for 8 hours to prepare a spinning solution with a sodium carbonate concentration of 2wt%; the spinning solution is transferred to a wet spinning device, the extrusion speed is set to 600r / min, the negative draft winding rate is set to 500r / min, the spinning solution is extruded into a coagulation bath containing 5wt% sulfuric acid, and the spinning solution undergoes an in-situ dynamic sol-gel transition in the coagulation bath to obtain a hollow aramid gel fiber; water is used as a displacement solvent, the aramid gel fiber is immersed in the displacement solvent for solvent displacement, and then freeze-drying is used to obtain a hollow aramid aerogel fiber. The obtained hollow aramid aerogel fiber was subjected to a mechanical property test, and the tensile strength of the hollow aramid aerogel fiber was measured to be 4.1 MPa.
[0068] Example 7
[0069] Potassium tert-butoxide was added to DMSO, and after ultrasonic dispersion, Kevlar aramid staple fibers with a length of 1-3 mm were added and stirred evenly, and mechanical stirring was performed for 3 days to prepare a dark brown-red aramid nanofiber dispersion (ANF), wherein the ratio of aramid staple fibers: potassium tert-butoxide: DMSO was 10 g: 20 g: 500 mL; potassium bicarbonate was then added to the ANF and stirred for 8 hours to prepare a spinning solution with a potassium bicarbonate concentration of 7 wt%; the spinning solution was transferred to a wet spinning device, and the extrusion speed was set. The spinning solution was controlled to be 600r / min, the negative draft winding rate was 500r / min, and the spinning solution was extruded into a coagulation bath containing 10wt% formic acid. The spinning solution underwent an in-situ dynamic sol-gel transformation in the coagulation bath to obtain a hollow aramid gel fiber; water was used as a displacement solvent, and the aramid gel fiber was immersed in the displacement solvent for solvent displacement, followed by supercritical drying, the supercritical temperature and pressure were 35°C and 9.5MPa, respectively, and the hollow aramid aerogel fiber was obtained after the pressure and temperature were reduced. The mechanical properties of the obtained hollow aramid aerogel fiber were tested, and the tensile strength of the hollow aramid aerogel fiber was measured to be 2.6MPa.
[0070] Comparative Example 1
[0071] The same as Example 2, except that sodium carbonate is replaced by isocyanate.
[0072] Comparative Example 2
[0073] The same as Example 5, except that sodium carbonate is replaced by isocyanate.
[0074] Comparative Example 3
[0075] Same as Example 1, except that no sodium carbonate is added.
[0076] The hollow aramid aerogel fibers prepared in the embodiments of the present invention and the comparative examples were observed using a transmission electron microscope. Figure 3 shown. Figure 3 a-3f are cross-sectional SEM images of aerogel fibers obtained in Comparative Example 3 and Examples 1-5, respectively. It can be seen that the aerogel fibers obtained by ANF without the addition of sodium carbonate do not have hollow tubes. As the concentration of sodium carbonate increases, the middle tubes of the aerogel fibers gradually increase. It can be seen that the diameter of the hollow tubes can be adjusted as needed, which has strong designability, and the fiber wall has a nanoporous structure.
[0077] Figure 3g-3h are SEM images of the cross-section of the aerogel fibers prepared in Comparative Examples 1-2, respectively. It can be seen that the aerogel fibers prepared in Comparative Examples 1-2 do not form a hollow structure. This may be because isocyanate reacts in the acidic coagulation liquid to generate amines and carbon dioxide, and its reaction kinetics with water are slow, and a large amount of carbon dioxide gas cannot be generated quickly. Therefore, it is difficult to be suitable for wet spinning and foaming of aramid nanofibers to prepare hollow fibers.
[0078] The hollow aramid aerogel fiber with a multi-level pore structure provided by the present invention has the characteristics of large specific surface area and high porosity. The inner diameter, outer diameter, wall thickness and pore size distribution of the fiber can be adjusted, thereby adjusting the pressure difference, flux and selectivity of the medium passing through the tube wall.
[0079] The hollow aramid aerogel fibers can be modified by filling them with functional materials, heat-treated, and hydrophobicized according to the use environment. They can also be used in phase change material adsorption, water-oil separation, filtration, seawater desalination, water treatment, high thermal insulation, energy storage and other fields, greatly expanding and improving the application scope and performance of aerogels and hollow fiber membranes.
[0080] In addition, the inventors also conducted experiments with other raw materials and conditions listed in this specification in accordance with the methods of Examples 1-7, and also produced hollow aramid aerogel fibers with a multi-level pore structure in which the hollow tube diameter can be adjusted as needed, a large specific surface area, and a high porosity.
[0081] Finally, it should be noted that the above description is only a preferred embodiment of the present invention. Under the guidance of the present invention, those skilled in the art can make a variety of similar expressions without violating the purpose and claims of the present invention, and such changes all fall within the protection scope of the present invention.
Claims
1. A method for preparing hollow aramid aerogel fibers, characterized in that: The following steps are involved: S1. The aramid fiber is placed in an alkali solution and stirred to obtain an aramid nanofiber dispersion; S2. adding a foaming agent to the aramid nanofiber dispersion to obtain a spinning solution; S3. Extruding the spinning solution into a mixed coagulation bath to obtain a hollow aramid wet gel fiber; S4. The aramid wet gel fiber is subjected to solvent replacement and dried to obtain a hollow aramid aerogel fiber.
2. The method for preparing a hollow aramid aerogel fiber according to claim 1, characterized in that: In S1, the length of the aramid fiber is 1-20 mm, for example, 1-15 mm, or 1-12 mm, or 1-10 mm, or 3-10 mm, or 3-8 mm, or 4-7 mm, for example, 5 mm.
3. The method for preparing a hollow aramid aerogel fiber according to claim 1, characterized in that: In S1, the alkali-containing solution is a polar organic solvent containing an alkaline substance; the mass volume ratio of the aramid fiber, the alkaline substance and the polar solvent is (1-10) g: (10-20) g: (300-500) mL.
4. The method for preparing a hollow aramid aerogel fiber according to claim 3, characterized in that: In S1, the aramid fiber is selected from one or more of para-aramid fiber, heterocyclic aramid fiber, and meta-aramid fiber; the alkaline substance is selected from one or more of potassium hydroxide, sodium hydroxide, sodium ethoxide, potassium ethoxide, sodium tert-butoxide, or potassium tert-butoxide; and the polar solvent is selected from one or more of DMSO, DMF, NMP, or DMAc.
5. The method for preparing a hollow aramid aerogel fiber according to claim 1, characterized in that: In S2, the foaming agent is an alkaline foaming agent; for example, one or more selected from carbonates and bicarbonates; for example, one or more selected from sodium carbonate, sodium bicarbonate, potassium bicarbonate, and ammonium bicarbonate; such as sodium carbonate.
6. The method for preparing a hollow aramid aerogel fiber according to claim 3, characterized in that: In S2, the amount of the foaming agent added is 0.25-15wt% of the total mass; for example, the amount added is 0.5-12wt% of the total mass; for example, the amount added is 1-10wt% of the total mass; for example, the amount added is 1-8wt% of the total mass.
7. A method for preparing a hollow aramid aerogel fiber according to any one of claims 1 to 6, characterized in that: In S3, the coagulation bath is selected from any one or more of sulfuric acid, hydrochloric acid, formic acid, acetic acid, oxalic acid, citric acid, phosphoric acid, and tartaric acid.
8. A method for preparing hollow aramid aerogel fibers according to any one of claims 1 to 6, characterized in that: In S4, the drying method is selected from a combination of one or more of supercritical CO2 drying, freeze drying or normal pressure drying; or is selected from one of supercritical CO2 drying and freeze drying.
9. A hollow aramid aerogel fiber, characterized in that: The hollow aramid aerogel fiber is prepared by the method described in claims 1 to 8, characterized in that the middle part of the hollow aramid aerogel fiber is a hollow structure, and the fiber wall is a nanoporous structure.
10. The hollow aramid aerogel fiber according to claim 9, characterized in that: The outer diameter of the fiber is 370 μm-430 μm, the inner diameter is 20 μm-300 μm, and the diameter of the nanopore is less than 200 nm.
Citation Information
Patent Citations
Graphene aerogel hollow fiber, and preparation method and application thereof
CN110607577A
Hollow aerogel fiber and preparation method thereof at normal temperature and normal pressure
CN118127654A
Preparation method of fiber-reinforced aromatic polyamide hollow fiber membrane and hollow fiber membrane prepared by preparation method
CN113117534A
Thermal insulation fiber cotton and preparation method thereof
CN117601513A
Hollow hard carbon aerogel fiber and preparation method thereof
CN117987967A
Cited By
Para-aramid fiber, para-aramid aerogel fiber and preparation method of para-aramid fiber and para-aramid aerogel fiber
CN120330908A
Para-aramid fibers, para-aramid aerogel fibers, and respective methods of making same
CN120330908B
Internal and external heterogeneous porous aramid fiber and preparation method thereof
CN121575499A
Intrinsically heterogeneous aramid porous fiber and method of making
CN121575499B